Griselda’s Afterlife, or the Relationship between Shakespeare’s The Winter’s Tale, Chaucer’s The Clerk’s Tale and the Tale of Magic - Wicher, Andrzej (Text Matters: A Journal of Literature, Theory and Culture, 2021)
Some influence of Chaucer’s The Clerk’s Tale, also known as the story of the patient Griselda, on Shakespeare, and particularly on The Winter’s Tale, has long been recognized. It seems, however, that the matter deserves further attention because the echoes of The Clerk’s Tale seem scattered among a number of Shakespeare’s plays, especially the later ones. The experimental nature of this phenomenon consists in the fact that Griselda-like characters do not strike the reader, especially perhaps the Renaissance reader, as good protagonists of a tragedy, or even a problem comedy. The Aristotelian conception of the tragic hero does not seem to fit Griselda because there is no “tragic fault” in her: she is completely innocent. It was thus a bold decision on the part of Shakespeare to use this archetype as a corner stone of at least some of his plays.